2018
DOI: 10.1111/jop.12763
|View full text |Cite
|
Sign up to set email alerts
|

Salivary S100A8/A9 in Sjögren's syndrome accompanied by lymphoma

Abstract: The results suggest that salivary levels of S100A8/A9 can aid in differentiating between SS, disease control and healthy control subjects, especially the subgroups of SS with lymphoma or at higher risk of lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…Many factors, including systemic diseases, can affect salivary production. Sjögren’s syndrome (SS) is a disease that affects salivary glands, manifesting as hyposalivation and abnormal levels of salivary components [ 2 ]. Sjögren’s syndrome can be classified as primary (pSS) or secondary (sSS) forms.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, including systemic diseases, can affect salivary production. Sjögren’s syndrome (SS) is a disease that affects salivary glands, manifesting as hyposalivation and abnormal levels of salivary components [ 2 ]. Sjögren’s syndrome can be classified as primary (pSS) or secondary (sSS) forms.…”
Section: Introductionmentioning
confidence: 99%
“…Sjogrens syndrome (SS) is an autoimmune disease that affects the exocrine glands of the body, including the salivary glands, and is associated with a significantly higher risk of developing lymphoma [ 130 ]. A recent study revealed that the levels of the pro-inflammatory heterodimer, S100A8/A9, in saliva could discriminate between healthy, SS, and mucosa-associated lymphoid tissue lymphoma (MALT-L), illustrating its potential as a salivary biomarker for the monitoring of SS progression [ 131 ]. Katz et al identified potential biomarkers of MM-associated bone disease in the saliva of MM patients.…”
Section: Salivamentioning
confidence: 99%
“…Screening the non-invasive biomarkers from the saliva and tears has a significant potential too. These fluids represent a crucial source of valuable biomarkers as LACTO or LIPOC-1 tear proteins or S100A8/A9, a molecule found in the saliva of pSS that correlates with a higher risk of developing lymphoma [15,16].…”
Section: Primary Sjogren Syndromementioning
confidence: 99%